Análisis Financiero a la Estación de Servicios de la Cooperativa de Transportes Loja de la ciudad de Loja, período 2021-2022. - Jiménez Largo, Jefferson Andrés (2024)
The Curricular Integration Work entitled Financial Analysis of Cooperativa de Transportes Loja ́s Service Station in the city of Loja, between 2021-2022, was carried out with the aim of finding a way to evaluate the economic-financial performance, using methods of analysis and interpretation and application of financial indicators to determine liquidity, debt and profitability in order to improve decision making to be more competitive and have a better position in the market. For the methodological process, it was essential to apply methods such as deductive, analytical, mathematical and statistical methods that allow the management of the information gathered, and thus present the results, enabling conclusions and recommendations to be drawn. The vertical and horizontal analysis of the financial statements was carried out, resulting in the percentages, amounts and variations produced in the accounts from one period to another, as well as the financial and economic structure; where current assets represent 82.88% and 69.67% in 2021 and 2022 respectively, made up of receipts generated by sales on credit that the station grants mainly to its members and other assets, such as the branches that the cooperative has, while on the liabilities side, the group that stands out the most is current liabilities with 39.93% and 8.10% respectively. With regard to the economic aspects, the production and sales costs are equivalent to 91.51% and 93.02% in 2021 and 2022 respectively, which has an impact on the low results obtained. The financial indicators were applied to determine the liquidity, debt| and profitability of the Cooperativa de Transportes Loja Service Station, demonstrating that it has the liquidity to meet its short-term obligations and to be able to invest. However, with respect to profitability in the year 2021, the net profit margin is low at 0.25% due to the high costs and expenses, which have caused it to make a loss in the year 2022. Finally, a financial analysis report was produced, which shows the economic reality of the gas station, as well as recommendations applicable to the relevant results, which serve as support for decision making.